Chronic cerebral hypoperfusion induces pathological venous remodelling via EPAS1 regulation - Wazny, Vanessa Kristina (Nanyang Technological University, 2025)
Cerebrovascular pathologies manifest in a zonation-dependent manner, though the impact of arteriovenous zonation on cognitive impairment remains unclear. We investigated the effects of cerebral hypoperfusion in mice through bilateral carotid artery stenosis, thereby recapitulating vascular dementia. We analysed endothelial subtype-specific responses in the prefrontal cortex using vascular phenotyping and single-cell transcriptomics. Venous cells exhibited the most significant structural and molecular changes related to vascular remodelling and angiogenesis, driven by Epas1 upregulation. In an isogenic model of human arterial and venous cells, 1% oxygen exposure led to sustained nuclear translocation of EPAS1 in venous cells. Pharmacological inhibition of EPAS1 alleviated abnormal cerebral venous sprouting and microglia activation. In subjects with mild cerebrovascular disease, lower cerebral blood flow was associated with increased circulating endothelial cells. Elevated levels of circulating venous cells correlated with white matter lesions and poorer cognitive function, suggesting venous cells as therapeutic targets for mitigating vascular cognitive impairment.